System readiness and the patient care pathway for Alzheimer's disease diagnosis and treatment - B. Joy Snider; Alessandro Biffi; Sasha Bozeat; Carolyn Clevenger; Gill Farrar; Darren Gitelman; Rachel Kolster; Soeren Mattke; Michelle Mielke; Debjani Mukherjee; Jennifer Murphy; Hamid Okhravi; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Promising therapeutic interventions that target the underlying pathophysiology are changing the landscape of Alzheimer's disease (AD) research. The AD care pathway must be transformed to meet the challenge of bringing these new therapies to the increasing number of people living with AD within the existing healthcare framework. Challenges include identifying patients who may benefit from treatment interventions early in the course of the disease, ensuring that diagnostic tools are accessible and accurate, and developing capabilities to monitor the effectiveness of interventions over time. These challenges must be addressed at all levels, from primary care settings to tertiary treatment centers; this will require collaborative efforts between health systems, drug manufacturers, and research institutions to navigate this evolving landscape and ensure system readiness for patients and their families with AD. The Spring 2024 Alzheimer's Association Research Roundtable (AARR) meeting gathered industry representatives and clinicians to discuss insights, challenges, and solutions that will help researchers and health systems identify patients in the early stages of AD and deliver emerging therapies efficiently and safely. In this paper, we provide highlights from the Spring 2024 AARR meeting.